PENGGUNAAN DEIKSIS DALAM NOVEL JILBAB TRAVELER: LOVE SPARKS IN KOREA KARYA ASMA NADIA - Ningsih, Silvina Ati; Charlina, Charlina; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study describes the use of deixis in novel Jilbab Traveler: Love Sparks In Korea by Asma Nadia. The purpose of this study was to identify the type and meaning of deixis used in the novel Jilbab Traveler: Love Sparks in Korea by Asma Nadia. This type of research is qualitative research with descriptive method, it means to analyze and describe data descriptively. This research data collection using documentation technique. Based on the analysis of data that has been done, found 352 deiksis with the division (a) deiksis persona 168 datas with the details of the first person dextis 44 ie I amount to 29 data, our exclusive amount of six data, inclusive we numbered nine datas, second personata 31datas you, and third persona 93 datas with details he has 44 datas, he has five datas, and they have 44 datas. (b) the deixis where 33 datas with details here have 10 datas, there have 11 datas, come have six datas, and to there have three datas. (c) Deixis time 110 datas with details of past time 12 datas that is then has five datas, yesterday has seven datas, time is going 92 datas ie now has 34 datas, now has 33 datas, and so far have 25 datas, and time which will come six datas ie tomorrow has five datas and front has one data. (d) dextis discourse 32 datas with details of discourse anaphora 26 datas and discourse katafora six datas. (e) social deiksis of nine datas with details of the use of eight datas euphemisms, and the mention of a single data title. Keywords : deixis, deixis type, deixis meaning.